Pathogenic Menace of MDR Bacteria in Stool and Throat Swab Surveillance Cultures of Hematopoietic Stem Cell Recipients and Evaluation of Post-Transplant Bloodstream Infections: A Cross-Sectional Study from A Tertiary Care Teaching Hospital of Kolkata, India - Kabita Choudhury; Sonia Deb; Suman Kundu; Baishali Dhar; Tuphan Kanti Dolai; Jayanta Bikash Dey; Swagata Ganguly Bhattacharjee (National Journal of Medical Research)
Background